Analisis Kesulitan Belajar Siswa dalam Menyesaikan Soal pada Materi Dimensi Tiga Kelas XII MIA SMA Negeri 1 Kota Tambolaka - Bora, Agustinus Rina; Lede, Yulius Keremata; Making, Samuel Rex M. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to describe the difficulties faced by students in solving problems in three-dimensional material with the subject being 2 students in class XII MIA. This research is a type of descriptive qualitative research. The data analysis technique used was a qualitative data analysis technique by selecting 2 students from 53 students to be used as interview subjects. Data collection was carried out using written tests and interviews. The research results obtained include factors that cause students to have difficulty understanding learning and solving problems in three-dimensional space material, namely students do not understand the concept of triangles, students' low interest in learning so that students become less attentive and lazy, do not understand the meaning of the questions, and students only memorize the concept, so they are given other questions and are confused